Management Support in Implementing A Career Path System for Nurses in Local Government Hospitals - Asmeriyanty Asmeriyanty; Yulastri Arif; Zifriyanthi Minanda Putri; Esthika Ariany Maisa (Indonesian Journal of Global Health Research, 2025)
Career ladder systems are an important mechanism in supporting the professional development of nurses and have been implemented in various models in a number of countries. Effective management support is critical to the successful implementation of career ladder systems in Indonesia. This study aims to determine the description of management support in the implementation of career ladder system in Local Government Hospitals. This study is a quantitative study with a cross-sectional design conducted in May-June 2024. The study population was all nurses who applied for competency assessment and credentialing/recredentialing as many as 76 people who also became samples with total sampling technique. Data were analyzed using descriptive statistics including frequency distribution and percentage. These questionnaires have undergone validity and reliability testing, with Cronbach's alpha values of 0.905 for the Management Support Questionnaire and 0.927 for the Nursing Career Path Questionnaire. The results showed that the majority of executive nurses were female (92%) with vocational education (84%) and were in early adulthood (26-35 years old). Most of them had between 8 to 15 years of service and almost half of them were at the Pre PK level (43%). Management support in implementing career ladders was mostly categorized as good (54%). This study concludes that management support in the implementation of the career ladder system in Local Government Hospitals is mostly good, but there are still some aspects that need to be improved. Optimal management support includes the provision of adequate resources, structured training programs, and continuous feedback to ensure the successful implementation of the career ladder system.